STRATEGI MULTI REPRESENTASI DENGAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Hutagaol, Kartini (Jurnal Padegogik, 2019)
This study aims to: (1) build trust, freedom in students through their chosen form of representation, (2) to know the improvement of students' mathematical problem solving ability, and (3) to know the interaction between learning factor and gain mathematical problem solving ability students. This research is an experimental research with control group design, pretest and postes. The population of this research is junior high school student of West Bandung Regency. While the sample is taken two classes at random class VIII students SMP Negeri 1 Cisarua representing middle school and two classes of students of class VIII SMP Negeri Satu Atap Kertawangi representing low school level students. The findings in this study are that the increase or gain of students who learn with multi- representation strategy is significantly different compared with the gain of mathematical problem solving ability of students who study with conventional. Students with a high prior knowledge prefer algebraic representation and are more skilled in using various forms of reprentation, early knowledgeable students prefer desk representation and low-priority students prefer schematic representations. Furthermore, the interaction is more effective for students with moderate and low knowledge. Keywords: Multi Representation Strategy, Student Mathematical Problem Solving Ability